Classification the Radioactive Waste in Russian Silo according to their Threat (D value) (International Journal of Current Engineering and Technology, 2014)
Recognizing that human health and safety is of paramount importance, the categorization system is, therefore, based on the potential for radioactive sources to cause deterministic health effects. This potential is comprised partly by the physical properties of the source and partly by the way in which the source is used. The actual practice in which the source is used, the provision of any inherent shielding provided by the device containing the source, portability, level of supervision and other judgmental criteria are taken into consideration. Radioactivity is a natural phenomenon and natural sources of radiation are features of the environment. Radiation and radioactive substances have many beneficial applications, ranging from power generation to uses in medicine, industry and agriculture. The radiation risks to workers and the public and to the environment that may arise from these applications as radioactive waste has to be assessed and, if necessary, controlled. Various methods have been used for classifying radioactive waste according to the physical, chemical and radiological properties that are relevant to particular facilities or circumstances in which radioactive waste is generated and managed. The aim of this study is classification of radioactive waste according to the threat they may cause. Based on that the sources should be characterized according to the A/D quotient, where A is the activity of the radioactive source and D is a pre-defined normalization factor. The concentrations activity of radionuclides founding in the radioactive wastes was measured using germanium detector. The higher quotient causes higher potential threat meant by the radioactive source to human health.
Keywords: D values, radioactive waste, dangers level.